(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article highlights the role of uzbek literature in the literary process of the world and examine research on the study of scientific issues related to poetics of national literature. Epic prose and modern national prose which is considered its principal part that have not been learnt the writers’ works in separate regions are the integral part of this research. The researching the originality of the prose texts of the creators of modern Uzbek literature and the cultural and educational life of Uzbekistan, as a sample of regional literature, in depth study is one of the most important scientific issues.